Seeing the End from the Beginning: The Plights of Children’s Education in the Conflict-Affected Areas in Katsina State, Nigeria - Abdullahi Muhammad; Mustapha Abdullahi (Asosiasi Profesi Pendidik dan Peneliti Sosiologi Indonesia (AP3SI), 2022)
A qualitative study examined children's educational and health well-being in areas affected by armed violence. Coordinated attacks on some villages and communities in Katsina State had rendered thousands of people homeless while some infants became orphans. The study was carried out in some designated Internally Displaced Camps in the seven most affected Local Government Areas in Katsina State. The researchers explored three qualitative data collection techniques in the study and elicited data from the field. Key Informant Interviews were conducted with camp officials, In-Depth Interviews were conducted with parents of the children aged 0-8 years taking refuge in the camps, and a non-participant observation method was used to observe the behaviour of the targeted children. The study revealed that children uprooted from their various villages were in dire need of assistance, particularly food, shelter, and medical attention. Also, there was no provision for temporary early childhood education services for the children who were supposed to be in school. Children traumatized by the gravity of the armed violence exhibit some elements of psychological disorder and difficulty in integrating with other displaced persons in the Camps and outsiders. The study concluded that children left without education at the most critical stage of life might become threats to society because they will grow without the requisite formal education that would enable them to become valuable members of their society.